Значение клинико-анамнестических данных в прогнозировании тяжести двигательных нарушений у больных спастическими формами детского церебрального паралича - Власенко, С.В. (Таврический медико-биологический вестник, 2010)
It is studied perynatal the anamnesis of 36 patients by a children’s cerebral paralysis, the form spastic diplegia. All patient performs operations apropos contractions. Morphological research of a site of a resulting muscle of a hip is carried out. All patients have been distributed on three groups on degree of expressiveness of pathological changes: the third - with as much as possible expressed phenomena of the regeneration, the second - the moderate pathological changes, the first – minimal structure destroys. Pathological clinical displays of disease have been equally expressed in all investigated groups. The carried out analysis anamnesis has shown data, that for patients of the first group was characteristic traumatic the proceeding childbirth, the second and the third - pathologically proceeding pregnancy, burdened obstetric the anamnesis. Thus collected anamnesis data allow to receive representation about weight of a pathology in each concrete case and to generate tactics of rehabilitation actions.